p53 codon 72 polymorphism and breast cancer risk: A meta-analysis - HOU, JING (D.A. Spandidos, 2013)
p53 is a tumor suppressor gene and plays important roles in the etiology of breast cancer. Studies have produced conflicting results concerning the role of p53 codon 72 polymorphism (G>C) on the risk of breast cancer; therefore, a meta-analysis was performed to estimate the association between the p53 codon 72 polymorphism and breast cancer. Screening of the PubMed database was conducted to identify relevant studies. Studies containing available genotype frequencies of the p53 codon 72 polymorphism were selected and a pooled odds ratio (OR) with 95% confidence interval (CI) was used to assess the association. Sixty-one published studies, including 28,539 breast cancer patients and 32,788 controls were identified. The results suggest that variant genotypes are not associated with breast cancer risk (Pro/Pro + Arg/Pro vs. Arg/Arg: OR=1.016, 95% CI=0.931–1.11, P=0.722). The symmetric funnel plot, Egger’s test (P=0.506) and Begg’s test (P=0.921) were all suggestive of the lack of publication bias. This meta-analysis suggests that the p53 codon 72 Pro/Pro + Arg/Pro genotypes are not associated with an increased risk of breast cancer. To validate the association between the p53 codon 72 polymorphism and breast cancer, further studies with larger numbers of participants worldwide are required.